IS COMPETITIVE INDUSTRY PERUVIAN CEMENT? - Arrarte Mera, Raúl Alberto (2012)
This study is part of applied research based on analysis of Comparative Financial Statements at December 31, 2011 - 2010, published by the Lima Stock Exchange, Peru. The cement sector is currently the most prominent on the national economy, driven by the private sector, the engine of the expansion of the sector, multifamily housing, shopping malls, supermarkets, hotels, and increased public investment, including construction and rehabilitation of roads, highways, hospitals, schools and other works in development and implementation The analysis is performed descriptive-explanatory documentary from published financial statements and reports of local rating agencies. The objectives in developing this work are: a) To examine whether the cement industry in Peru, is competitive and contributes to cost reduction. b) Check if the cement industry benefited from the housing boom improving productivity. c) To determine whether performance measure of economic value added in the cement sector was positive in the current years 2010 and 2011. The industry is competitive because it has increased the unit price of the stock despite the growth of cement consumption; benefited from the housing boom. The economic value added, a TEA 1 of 7%, in local currency, was positive for all cement companies except Cemento Andino SAA. We urge shareholders to promote a widespread approach STATEUNIVERSITY- ENTERPRISE seeking greater productivity with high added value.